(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The aim of design of oral extended drug delivery system is to achieve a prolonged therapeutic effect by continuously releasing medicament over an extended period of time after administration of a single dose. An attempt was made to formulate Tramadol Extended Release (ER) matrix tablet using combination of hydrophobic and hydrophilic polymer consisting of ethyl cellulose, HPMC K15M, carbopol, and xanthan gum. The polymeric concentration of hydrophobic and hydrophilic polymer was optimized and was found that drug to polymeric ratio (hydrophobic and hydrophilic) of 1:0.75:0.75 was appropriate for the formulation of Tramadol ER tablet. The concentration of hydrophobic polymer was kept constant were as the combination of hydrophilic polymer was attempted and combined to hydrophobic polymer to retard the drug release for 24-hour from the matrix tablet. A total of nine formulations (F1-F9) of Tramadol matrix tablet, with different concentration of hydrophobic and hydrophilic polymer were used with other excipients. The tablets were compressed by direct compression method after subjecting the blend to blend physical parameters studies like studies like angle of repose, bulk density, tapped density, Carr’s index. The results obtained were satisfactory. Post compression parameters like hardness, weight variation, friability, drug content analysis and in-vitro release profiles of drug from all the formulations could be best expressed by Higuchi’s equation, as the plots showed high linearity (R2: 0.942-0.995). To confirm the diffusion mechanism, the data were fit into Korsmeyer equation. The formulations F-1 to F-6 showed good linearity (R2: 0.961 to 0.993), which indicate the mechanism is diffusion coupled with erosion.